DEVELOPMENT OF A POLE-SWITCHING WINDING ONPOLE RATIO 8:4. - Rozmetov Khamza Ernazarovich, (TADQIQOTLAR.UZ, 2024)
Annotation:The article discusses the process of development and research of a new pole-switching winding with a pole ratio of 8:4 for two-speed motors driving twin-shaft mixers.